Tolerance Education in the Hidden Curriculum: A Case Study on Indonesian Public School - Kurniawan, Kevin Nobel (Masyarakat: Jurnal Sosiologi, 2018)
Religious intolerance is spreading within the Indonesian institution of education. Previous studies have shown that the growth of intolerance is due to the state’s regulation and pedagogical apparatus. In contrast to the previous studies, I argue that the intolerance is related to a hidden curriculum applied by the institution of education. Normatively, the hidden curriculum contains the value of religious tolerance. However, factually, I found evidence of practices of intolerance, through both the formal and informal spheres within the school structure, in a hidden curriculum. This article is written based on a qualitative approach with a mixed-method research strategy to analyze data collected from students, teachers, and alumni through field observation, in-depth interviews, and surveys.